2023
DOI: 10.1002/oto2.25
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Electronic Cigarettes on the Upper Aerodigestive Tract: A Comprehensive Review for Otolaryngology Providers

Abstract: Objective The use and effects of electronic (e)‐cigarettes (e‐cigs) are particularly relevant for otolaryngology providers as tobacco plays a major role in benign and malignant diseases of the upper aerodigestive tract. This review aims to (1) summarize the recent policies regarding e‐cigs and important patterns of use and (2) serve as a comprehensive resource for clinical providers on the known biologic and clinical effects of e‐cigs on the upper aerodigestive tract. Data Sources … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 226 publications
(554 reference statements)
0
1
0
Order By: Relevance
“…Findings from a study of maternal e-cigarette use suggest that maternal use may be harmful to offspring development [30]. Pediatric studies have found that e-cigarette use by youth has negative physical and mental health consequences, and there has been an effort to restrict e-cigarette use by youth because of findings of damage to the upper aerodigestive tract [31,32]. For example, the US FDA has been urging pediatricians to perform screenings of youth for e-cigarette product use with preventive messages and appropriate treatment options when use is discovered [33].…”
Section: Respiratory Effectsmentioning
confidence: 99%
“…Findings from a study of maternal e-cigarette use suggest that maternal use may be harmful to offspring development [30]. Pediatric studies have found that e-cigarette use by youth has negative physical and mental health consequences, and there has been an effort to restrict e-cigarette use by youth because of findings of damage to the upper aerodigestive tract [31,32]. For example, the US FDA has been urging pediatricians to perform screenings of youth for e-cigarette product use with preventive messages and appropriate treatment options when use is discovered [33].…”
Section: Respiratory Effectsmentioning
confidence: 99%